Analysis of Total Displacement Value in Mine Opening with and Without Supports in Weak Rock - Ira, Nurmaya Putri; Dwi Puteri, Martsa Farindi; Catherine, Liany Ayu (Jurnal Teknik Sipil, 2025)
The stability of underground openings in weak rocks presents a major challenge in geotechnical engineering due to the time-dependent deformation and low mechanical strength of such materials. This study analyzes total displacement in tunnel structures with and without support systems, focusing on the Cileunyi "“ Sumedang - Dawuan toll road tunnel in West Java. Using a 3D finite element modeling approach (Phase2 software), comparisons were made between two tunnel spacing configurations (3R and 5R). The results show that the installation of support systems such as steel ribs, wire mesh, and shotcrete significantly reduces displacement, especially on critical zones like the tunnel"™s left wall. The 3R model recorded a maximum displacement difference of 46.3 mm, while the 5R model showed 44.9 mm. This study confirms that proper support configuration not only minimizes deformation but also promotes more uniform stress redistribution. The findings highlight the importance of integrating empirical data with numerical simulations for effective tunnel support design in weak rock environments.